PELAKSANAAN PRINSIP KEPESERTAAN BERSIFAT WAJIB PADA SISTEM JAMINAN SOSIAL KETENAGAKERJAAN - Noviansyah, Azizi (Faculty of Law, University of Palembang, 2019)
The result of this research is the implementation of the Mandatory Membership Principle On Labor Social Security System are through Evaluation of Membership, Membership Additions Growth Analysis, Analysis of Active Participation, support from the Human Resources and through BPJS Ketenagakerjaan Branch Office Palembang Operations and Services programs. The limiting factors of the Implementation are : the existence of other private insurance agencies; the lack of public and companies awareness; administrative sanctions on employers; limited informal sector workers membership growth; and the differences in the calculation of the value of contributions to be paid by the company. Supporting factors are : efforts of the government to rise Law No. 24 of 2011 concerning the Social Security Administrator Agency (BPJS); firmness of the law enforcers; good coordination among agencies from central to local levels; socialization by cooperating with the mass media; service and the ease of access registration system through E-Channel.